Mendorong Loyalitas Melalui Kualitas Pelayanan dan Kepercayaan: Encouraging Loyalty Through Quality Service and Trust - Irwan Kurniawan; Rr Maidarti; Ris Handayani (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2021)
Among the many factors that affect customer loyalty, this study focuses more on the effect of service quality and trust on customer loyalty. This study aims to determine the effect of service quality and trust on customer loyalty of SME’s products. The survey method involved respondents through a purposive non-random sampling technique of 40 consumers who had used online purchasing services. Primary data obtained by distributing questionnaires. The choice of answers on the questionnaire uses the Guttman Scale, which is a scale used for clear answers, which only consists of two answer choices, agree or disagree. Several tests were applied in the form of validity, reliability and normality tests, partial and multiple correlation, regression, t test and F test. Some of the findings in this study are that there is a positive and significant influence between the service quality variable on the customer loyalty variable at a positive and strong level of influence. There is a positive and significant influence between the trust variable on customer loyalty which is positive and the effect is very strong, and simultaneously service quality and trust have a positive and significant effect on customer loyalty for MSME’s products.